T132. PATIENT AND PHYSICIAN FACTORS ASSOCIATED WITH FIRST DIAGNOSIS OF PSYCHOTIC DISORDER IN PRIMARY CARE. (9th April 2019) - Anderson, Kelly; Archie, Suzanne; Booth, Richard; Cheng, Chiachen; Hameed, Saadia; MacDougall, Arlene; Palaniyappan, Lena; Ryan, Bridget; Voineskos, Aristotle; Rodrigues, Rebecca
Abstract: Background: The family physician has been identified as a key player on the pathway to care in first-episode psychosis, as the majority of young people with early psychosis make help-seeking contacts in primary care. This involvement of family physicians has been shown to reduce the likelihood of negative pathways to care. As such, increasing the involvement of family physicians in the identification of early psychosis would be beneficial for improving service-related outcomes. Our objectives were to estimate the proportion of youth with early psychosis who are diagnosed in primary care, and to identify patient- and physician-level factors associated with a first diagnosis of psychosis in primary care. Methods: Using population-based health administrative data, we constructed a retrospective cohort of people aged 14 to 35 years with a first diagnosis of psychosis in Ontario between 2005 and 2015. We extracted data on all mental health help-seeking attempts in primary care in the six-month period preceding the first diagnosis of psychotic disorder. Restricting the sample to people with help seeking attempts in primary care, we used multilevel logistic regression models, with physician as the clustering unit, to model the patient and physician characteristics associated with first diagnosis in primary care. Results: Nearly two thirds (63%) of young people with early psychosis (n = 39, 449) had mental health help-seeking contacts in primary care in the six-month period prior to first diagnosis. Of those, 47% were diagnosed in primary care (30% of total cohort), whereas 53% received their diagnosis in secondary or tertiary care services (33% of total cohort). Initial results suggest that people who are older at psychosis onset are more likely to receive their first diagnosis in primary care, and people who have a history of other psychosocial comorbidities are less likely to be diagnosed in primary care. Full results for patient- and physician-level factors associated with a first diagnosis in primary care will be presented. Discussion: Approximately one in three young people with early psychosis in Ontario receive their first diagnosis of psychotic disorder from a family physician, and an additional third of people with early psychosis made help-seeking attempts in primary care for mental health reasons but received their first diagnosis in secondary or tertiary care services. The findings from these analyses will allow us to identify subgroups of primary care providers to target with continuing medical education efforts to better support family physicians in their central role in pathways to care for first-episode psychosis.